Sistem Informasi Pembelian Dan Penjualan Pada Toko Zhafirah Cosmetics Berbasis Dekstop - Huwaida, Aspiya; Upayarto, Budi (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2025)
The research aims to develop a system for Zhafirah Cosmetics Store to address operational issues such as manual transaction recording, lack of transaction receipts, and time-consuming documentation processes. A desktop-based sales and purchase information system was developed using a descriptive research method, with data collected through observation and interviews, system analysis conducted using the PIECES framework, and system development following the waterfall model. The implementation results show that the system effectively accelerates transaction recording, minimizes input errors, and generates accurate and efficient reports. It also simplifies the management of product, supplier, and transaction data, thereby supporting managerial decision-making. System testing was conducted using Black Box Testing and User Acceptance Testing (UAT), with UAT results showing an average score of 88.67%, categorized as “Very Good,” indicating strong user acceptance. The implication of this research is an improvement in operational effectiveness and a reduction in data loss risk through the digitization of the store’s business processes.